Current Trends in Endodontic and Periodontal Treatment - Аdilova Aziza Shukhrat qizi (Genius Journals, 2023)
Endodontics is a branch of dentistry that studies the structure, functions of the pulp and periapical tissues, it is aimed at studying the physiological state and diseases of the pulp and periodontium, as well as their prevention. The modern concept of endodontic treatment is to eliminate infection from the root canal, treat the foci of periapical lesions to restore the integrity of the periodontal tissue barrier, and prevent microbial invasion. This article discusses the current trends in endodontic and periodontal treatment and provides examples.
Keywords: Endodontics; periodontology; plasma therapy